(3MSf GdJYHjQ YeG ddMQR ef GdJcHjQs - (3CMeO GdOefghQjs; (3GdbGSe Hf ajQg Hf Nda Hf CMeO GdQYjfj, CHh eMeO GdTGWHj,J (B590 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd CMeO GdOefghQj GdMbjQ gPG HjGf eG ddTGWHjI ef GdJcHjQ eY eSGFd jJYjf Gdhbha YdjgG s
(3BNQgG (B:s
(3MPa GdgeRI eY JMbjb s
(3GdfSNI HgG MhGTs
(3MQR GdCeGfj aj cTa GdXfhf L (B646/1s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdbQGAGJ hGdJLhjOs